STUDI KASUS: KETIDAKNYAMANAN PADA KEHAMILAN DENGAN PRESENTASI BOKONG - Sitti Sarifah Kotarumalos; Leonita Angela Herwawan (Jurnal Kebidanan, 2021)
Pregnancy with a breech presentation is a condition in which the fetus lies lengthwise with the head in the uterine fundus and the buttocks at the bottom of the uterine cavity. Pregnant women with a presentation of buttocks in the third trimester experience physical and psychological discomfort. During pregnancy, women need time to adapt to the various changes that occur in them. Because these changes generally cause discomfort and worry for most pregnant women. Physical discomfort felt is a feeling of fullness and tightness in the upper abdomen, increased frequency of urination, constipation and back pain. While the anxiety or psychology of the mother in the face of childbirth is one of the discomforts experienced by pregnant women. This case study was conducted on a pregnant woman G2P1A0, Gravida 36 weeks with breech presentation. Complaints that are felt are feeling tight in the upper abdomen, frequent urination at night and constipation. Mother complained of back pain. Mothers also feel anxious about the delivery process. Based on these complaints, the midwifery care provided to overcome the mother's complaints is to inform the third trimester of discomfort with breech pregnancy, and educate how to overcome the discomfort.